Macaulay's theory of duration: 80-year thematic bibliometric review of the literature. Issue 1 (28th April 2020) - Shah, Syed Alamdar Ali; Sukmana, Raditya; Fianto, Bayu Arie
Abstract : Purpose: The purpose of this research is to propose a framework for research on Macaulay duration and establish future research directions. Design/methodology/approach: Thematic, bibliometric and content analyses have been used to review 168 research papers published between 1938 and 2019 taken from ISI Web of Science and Scopus contributed by leading authors, journals and regulatory bodies. Findings: Identification and integration of themes of duration theory, duration model development and duration model implementation leading to unattended research gaps, and framework for research on Macaulay duration. Research limitations/implications: The study is based on an extensive review of the literature to extract important themes, research gaps and frameworks. It does not empirically investigate significance of Macaulay duration and various sectors. Practical implications: This research has several aspects that are helpful for practitioners. Macaulay duration has been the subject of empirical research only without any guiding framework. This research provides a platform to initiate profound researches in various areas of finance. Various proposed models are required to be tested under holistic approach in conventional and emerging fields, especially in Islamic settings. Originality/value: This research highlights, research themes leading to framework, research gaps and factors that are crucial in developing, extending and testing duration models leading to enhancement of theoretical base of Macaulay duration.